(untitled) (LEGAL DIALOGICA, 2025)
This study aims to analyze the effectiveness of law enforcement carried out by the Indonesian Police against perpetrators of narcotics crimes in Polewali Mandar Regency and to determine the obstacles that influence the effectiveness of law enforcement by the Indonesian Police against perpetrators of narcotics crimes in Polewali Mandar Regency. This study uses an empirical research method, where the research was carried out at the Polewali Mandar Police Resort. The data used includes primary and secondary data. Data collection was carried out through field studies and literature studies. Data analysis, the author uses a qualitative analysis approach. The results of this study indicate that the effectiveness of law enforcement by the Indonesian Police against perpetrators of narcotics crimes in Polewali Mandar Regency has not shown effective law enforcement. This is reflected in the existence of various obstacles and the continued discovery of new cases every year. Meanwhile, a number of obstacles that influence the effectiveness of law enforcement include the limited number of investigators compared to the area of ​​Polewali Mandar Regency, technological advances utilized by perpetrators to avoid tracking, the use of a closed network system by perpetrators which causes them to protect each other when one of the members is caught, and the actions of perpetrators who often destroy or destroy evidence of narcotics. Abstrak: Penelitian ini memiliki tujuan untuk menganalisis efektivitas penegakan hukum yang dilakukan oleh Kepolisian RI terhadap pelaku tindak pidana narkotika di Kabupaten Polewali Mandar dan mengetahui hambatan-hambatan yang memengaruhi efektivitas penegakan hukum oleh Kepolisian RI terhadap pelaku tindak pidana narkotika di Kabupaten Polewali Mandar. Penelitian ini menggunakan metode penelitian empiris, tempat penelitian dilaksanakan di Kepolisian Resor Polewali Mandar. Data yang digunakan meliputi data primer dan sekunder. Pengumpulan data dilakukan melalui studi lapangan dan studi kepustakaan. Analisis data, penulis menggunakan pendekatan analisis kualitatif. Hasil penelitian penelitian ini menunjukkan efektivitas penegakan hukum oleh Kepolisian RI terhadap pelaku tindak pidana narkotika di Kabupaten Polewali Mandar belum menunjukkan penegakan hukum yang efektif. Hal ini tercermin dari adanya berbagai hambatan dan masih ditemukannya kasus-kasus baru setiap tahunnya. Adapun, sejumlah hambatan yang memengaruhi efektivitas penegakan hukum tersebut, antara lain keterbatasan jumlah penyidik dibandingkan dengan luas wilayah Kabupaten Polewali Mandar, kemajuan teknologi yang dimanfaatkan pelaku untuk menghindari pelacakan, penggunaan sistem jaringan tertutup oleh pelaku yang menyebabkan mereka saling melindungi ketika salah satu anggota tertangkap, serta tindakan pelaku yang sering kali menghancurkan atau memusnahkan barang bukti narkotika.